Implementation and enhancement of risk management in frozen food Processing at UD. FFI Driyorejo Gresik - Andari, Laila Ayu; Kurniyanto, Ifan Rizky (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Indonesian SMEs are vital for economic growth. UD. FFI Driyorejo Gresik, a frozen food SME, faces production planning and efficiency challenges due to demand fluctuations and absent risk management. This research identifies and prioritizes risks, recommending mitigation strategies. Methods: Qualitative data was collected via interviews at UD. FFI. The House of Risk (HOR) method was used to identify, assess, and prioritize risk agents, utilizing SCOR mapping, severity/occurrence assessments, and Pareto analysis. Results: Eighteen risk events and twenty-four risk agents were identified. "Insufficient raw material supply" had the highest Aggregate Risk Potential (ARP). Pareto analysis revealed eleven priority risk agents comprising ~80% of total risk. Recommended mitigation included improved inventory, SOP monitoring, maintenance, training, and proactive management. Conclusion: UD. FFI is vulnerable in supply chain and production, primarily from raw material issues and process inconsistencies. Inventory management improvement is crucial for better efficiency, quality, and resilience. This study offers a risk management framework for frozen food SMEs. Future research could explore long-term effectiveness and external supply chain factors.